The Potentional Relationship Between Gingival Recession And Bone Thickness In The Context Of Orthodontic Treatment - Adisty Restu Poetri; Shella Indri Novianty (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background : The term